Criminal Law Policy on Euthanasia Practices by Doctors in Indonesia from the Perspective of Justice and Protection of Patient Rights - Sholikhatun Sholikhatun; Sri Endah Wahyuningsih (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Indonesia, as a state based on law, places the supremacy of law as a foundation, including the protection of the right to life as stipulated in Article 28A of the 1945 Constitution. Euthanasia becomes a complex issue because it involves a dilemma between the right to life, human dignity, and the suffering of terminal patients. Article 344 of the Criminal Code prohibits ending life upon request; however, developments in medical technology create challenges in legal interpretation. Several countries have legalized euthanasia under strict conditions, unlike Indonesia, which has no specific regulation. This legal vacuum causes uncertainty for doctors and patients, thus requiring reconstruction of criminal policy that is relevant, just, and proportionally protects human rights. The research aims to describe and analyze the criminal law provisions currently in force in Indonesia regulating euthanasia by doctors and to describe and analyze the ideal criminal law policy in regulating euthanasia by doctors so that it is in line with justice and the protection of patient rights in Indonesia. This normative juridical research is descriptive, using secondary data from primary, secondary, and tertiary legal materials, analyzed qualitatively through a literature study to examine criminal policy on euthanasia in Indonesia. The results of this research show that the criminal law provisions currently in force in Indonesia regulate euthanasia by doctors, yet euthanasia regulation in Indonesia still triggers debate. Some support it as a human right to decide life or death, while others reject it because it contradicts religion and Pancasila. The Criminal Code regulates crimes against life in Articles 338–350, including murder, assisting suicide, and abortion. The new Criminal Code, Law Number 1 of 2023, does not directly regulate euthanasia, but Article 428 paragraph (1) regulates passive euthanasia with a penalty of 2.5 years imprisonment or a fine, and Article 461 regulates active euthanasia at the request of the victim with a penalty of nine years imprisonment. Both articles affirm the prohibition of euthanasia even at the request of the victim, and the ideal criminal policy in regulating euthanasia by doctors must be in line with the values of justice and protection of patient rights in Indonesia. The ideal criminal policy regarding euthanasia in Indonesia must balance the protection of patients’ right to life, the professional responsibilities of doctors, and moral and religious values. Regulations must include sanctions, procedures, ethical guidelines, and monitoring mechanisms. Exceptions may be granted for terminal medical conditions with written consent, physician verification, and ethics team recommendation. Criminal sanctions should be the ultimum remedium, preceded by ethical and administrative mechanisms. Synchronization with the Health Law, the Medical Practice Law, and the code of ethics is important to avoid conflicts of norms. Supervision by an independent ethics committee prevents misuse. Public participation, periodic evaluation, as well as training for medical personnel and law enforcement officers will strengthen patient protection and legal certainty for healthcare professionals.